1994
DOI: 10.3109/08039489409081375
|View full text |Cite
|
Sign up to set email alerts
|

Mianserin added to tricyclic antidepressants in depressed patients not responding to a tricyclic antidepressant alone: A randomized, placebo-controlled, double-blind study

Abstract: Medhus A, Heskestad S, Tjemsland L. Mianserin added to tricyclic antidepressants in depressed patients not responding to a tricyclic antidepressant alone. A randomized, placebo-controlled, double-blind study. Nord J Psychiatry 1994;48:355-358. Oslo. ISSN 0803-9488.The purpose of this study was to investigate whether depressed patients not responding to tricyclic antidepressants (TCA) would respond on addition of 3060 mg mianserin. Thirtyseven in-and out-patients still fulfilling DSM-III criteria for a major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…There are two double-blind controlled studies of TCAs used in combination with mianserin (Lauritzen 1992;Medhus 1994). These reported encouraging results, although the numbers were small (total n = 57) and the treatment period was brief.…”
Section: Tca With Mirtazapine or Mianserinmentioning
confidence: 99%
“…There are two double-blind controlled studies of TCAs used in combination with mianserin (Lauritzen 1992;Medhus 1994). These reported encouraging results, although the numbers were small (total n = 57) and the treatment period was brief.…”
Section: Tca With Mirtazapine or Mianserinmentioning
confidence: 99%
“…Another double-blind study (n = 31) has shown higher response rates among patients treated with fluoxetine plus mianserin than among those treated with fluoxetine alone at initiation of treatment [58]. Mianserin augmentation has been reported anecdotally to be effective in depressed patients unresponsive to TCA alone [145], and fluoxetine nonresponders achieved greater efficacy when mianserin was added to fluoxetine than when placebo was added [146]. A more recent study found adding mianserin in sertraline nonresponders had no advantage over adding placebo [147], but the initial trial with sertraline monotherapy was too brief and a dose increase of sertraline was carried out 2 weeks prior to randomization, thereby confounding the results.…”
Section: Combination Studiesmentioning
confidence: 99%
“…Finally, although the SSRIs sertraline and fluoxetine presumably have equivalent efficacy (Aguglia et al 1993), they are different compounds, perhaps with differential potentials when combined with mianserin. Previous studies have indicated that the addition of mianserin to a TCA may increase the antidepressant response (Lauritzen et al 1992;Medhus et al 1994). …”
Section: Discussionmentioning
confidence: 98%